GROWTH OF CARBON NANOTUBE FROM NANOSTRUCTURED COMPOSITE OF Fe-C USING ION IMPLANTATION TECHNIQUE - Salim Mustofa (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2010)
GROWTH OF CARBON NANOTUBE FROM NANOSTRUCTURED COMPOSITE OF Fe-C USING ION IMPLANTATION TECHNIQUE. Growth of carbon nanotube (CNT) from nanostructured composite of Fe-C has been carried out using ion implantation technique. The CNT developed here is expected to be used as an Integrated Sensor System, because CNT offer promises for future nano-electronic sensor applications, and reliably controlling CNT growth has been a big challenge. Nanostructured composite of Fe-C was prepared by milling for 50 hours. The size of Fe-C powder was determined from Scanning Electron Microscope (SEM) image. Milled powder then was compressed to get pellet form of Fe-C, and used as a target in fabricating thin film of Fe-C on Si(100) substrate using sputtering technique. Further, the ion implantation was done against the Fe-C thin film. The ion source using Argon gas, in order to make growth of CNT until the densitiy dose of 5 x 1015 ions/cm2 . The phase of formed CNT was identified by X-Ray Diffractometer (XRD), the morphology of surface was observed by SEM. From this research, it has been showed that the milled composite of Fe-C has a powder size until nano order size. From XRD data, it is identified that only Fe and C peaks were confirmed. On the other hand, the observation on the surface of Fe-C thin film showed the growth of CNT